Sistem Pakar Berbasis Web Untuk Menentukan Pembagian Harta Waris Menurut Hukum Islam Menggunakan Metode Forward Chaining dan Dempster-Shafer - Dhavin Putra Alamsyah; Sutrisno Sutrisno; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Islamic law establishes inheritance rules with a very fair form. In it is the right of ownership of property for the heirs, both men and women in a fair way. Islamic law also establishes the right of shifting of ownership of a person after passing away to his heirs from all his relatives and nasabs, without distinction between men and women, young and old alike. But in its implementation, for the Islamic community itself, most of the determination and calculation of inheritance is done in a way that is not in accordance with the prevailing law of inheritance of Islam that often leads to conflict. In solving the limited problem of experts regarding inheritance law, it is necessary to design an application that can help solve the problem according to Islamic law. This thesis provides a more accurate decision using forward chaining and dempster-shafer methods based on an expert's trust. In the Dempster-Shafer theory there is a Frame of Discernment denoted by Î¸. This frame is the universe of speech from a set of hypotheses Î¸ = {A, B, D, E}. The goal is to relate the trust size of the elements Î¸. Not all evidences directly support each element. Based on the testing of this system that is equal to 92.67% which means this system can run well because the results of the system close to the similarity with the fact of the actual field.